FLY ASH PLTU SUMBER ALAM SEKURAU KALIMANTAN UTARA SEBAGAI BINDER BETON GEOPOLIMER - Hertianisya, Nurul Hanipah; Prasetya, Noerman Adi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
ABSTRACT: Geopolymer concrete uses pozzolanic materials such us fly ash to replace the role of cement. This study aims to design a geopolymer concrete mixture to obtain a compressive strength value based on the age or variation of the concrete mix and identify the effect of variations in alkaline activator solution on the compressive strength of geopolymer concrete. Fly ash which reacts with alkaline activator liquid in a ratio of 50:50, funcitions as a binder, where the alkaline activator used in this study is Na2Si03, and NaOH concentration of 10M with the test variable used is variation one at a ratio of 50:50; variation two at a ratio of 60:40 and variation three at a ratio of 66,67:33,33, while the filler composition and binder were 75:25. In this research, 27 samples were made of cylindrical specimens by testing the compressive strength of concrete at the age of 7, 21 and 28 days. The mixing method used in this research was the wet mixing method. Based on the research result, the average compressive strength at seven days for each variation was 11,533 Mpa; 9,300 Mpa and 12,367 Mpa. At 21 days each variation in a row was 9,300 Mpa; 11,567 Mpa and 14,800 Mpa. Each variation’s concrete with 28 days of age successively was 10,500 Mpa; 14,400 Mpa and 12,533 Mpa. In addition, the variation in the alkaline activator solution between Na2Si03, and NaOH affects the results of the compressive strength of geopolymer concrete.Keywords: alkaline activator, geopolymer concrete, fly ash, compressive strengthABSTRAK: Beton geopolimer merupakan beton yang menggunakan bahan pozzolan seperti fly ash untuk menggantikan peran semen. Tujuan dari penelitian ini yaitu membuat desain campuran beton geopolimer sehingga mendapatkan nilai kuat tekan berdasarkan umur ataupun variasi campuran beton dan mengidentifikasi pengaruh dari variasi larutan alkali aktivator terhadap kuat tekan beton geopolimer. Fly ash yang bereaksi dengan cairan alkali aktivator dengan perbandingan 50:50 berfungsi sebagai bahan pengikat, dimana alkali aktivator yang digunakan dalam penelitian ini yaitu Na2SiO3 dan NaOH konsentrasi 10M dengan variabel pengujian yang digunakan ialah variasi 1 pada rasio 50:50; variasi 2 pada rasio 60:40 dan variasi 3 pada rasio 66,67:33,33 sedangkan komposisi filler dan binder sebesar 75:25. Pada penelitian ini dibuat benda uji berbentuk silinder sebanyak 27 sampel dengan pengujian kuat tekan beton pada umur 7, 21 dan 28 hari. Metode percampuran yang digunakan dalam penelitian ini yaitu pencampuran dengan metode basah. Berdasarkan hasil penelitian diperoleh rata-rata kuat tekan pada umur 7 hari setiap variasi secara berturut-turut yaitu 11,533 Mpa; 9,300 Mpa dan 12,367 Mpa. Pada umur 21 hari setiap variasi secara berturut-turut yaitu 9,300; 11,567 Mpa dan 14,800 Mpa. Beton dengan umur 28 hari pada setiap variasi secara berturut-turut yaitu 10,500 Mpa; 14,600 Mpa dan 12,533 Mpa. Selain itu adanya variasi dalam larutan alkali aktivator antara Na2SiO3 dan NaOH mempengaruhi hasil dari nilai kuat tekan beton geopolimer.Kata Kunci: alkali aktivator, beton geopolimer, fly ash, kuat tekan